Elevated serum CA 19–9 level mimicking pancreaticobiliary carcinoma from a hepatic abscess: case report and literature review - Shaurya Dhingra; Puneet Raman; Taylor Ramsaroop; Isaiah Harrison; Tova Bergsten; Erin Nusbaum; Lawrence E. Feldman; Lawrence E. Feldman (Frontiers in Medicine)
Serum levels of the tumor marker CA 19–9 are widely utilized in the diagnosis and monitoring pancreatic and biliary malignancies. However, serum levels of CA 19–9 have also been reportedly elevated in non-malignant conditions. Here, we present the rare case of a 65-year-old woman with a history of gallbladder malignancy who was found to have a new hepatic lesion on surveillance CT with an associated elevation in CA 19–9 to 5,866 U/mL. Drainage of the lesion and treatment with antibiotics resulted in a rapid decline in CA 19–9 levels, indicating that the elevation in CA 19–9 was due to a benign hepatic lesion. We review eight similar reported cases of CA 19–9 elevations due to benign hepatic abscesses, thereby highlighting a need to interpret the tumor marker with caution.